Long-term Follow-up Study of Fecal Microbiota Transplantation for Severe and/or Complicated Clostridium difficile Infection: A Multicenter Experience. Issue 5 (May 2016) - Aroniadis, Olga C.; Brandt, Lawrence J.; Greenberg, Adam; Borody, Thomas; Kelly, Colleen R.; Mellow, Mark; Surawicz, Christina; Cagle, Leslie; Neshatian, Leila; Stollman, Neil; Giovanelli, Andrea; Ray, Arnab; et al.
Abstract : Goal: Our aim was to investigate fecal microbiota transplantation (FMT) efficacy in patients with severe and/or complicated Clostridium difficile infection (CDI). Background: FMT is successful for recurrent CDI, although its benefit in severe or complicated CDI has not specifically been evaluated. Study Methods: A multicenter long-term follow-up study was performed in patients who received FMT for severe and/or complicated CDI (diagnosed using standard criteria). Pre-FMT and post-FMT questionnaires were completed. Study outcomes included cure rates and time to resolution of symptoms. Results: A total of 17 patients (82% inpatients, 18% outpatients) were included (76.4% women; mean age, 66.4 y; mean follow-up, 11.4 mo). Patients had severe and complicated (76.4%) or either severe or complicated (23.6%) CDI. Sixteen patients (94.1%) had diarrhea, which resolved in 12 (75%; mean time to resolution, 5.7 d) and improved in 4 (25%) after FMT. Eleven patients (64.7%) had abdominal pain, which resolved in 8 (72.7%; mean time to resolution, 9.6 d) and improved in 3 (27.3%) after FMT. Two of 17 patients experienced early CDI recurrence (⩽90 d) after FMT (primary cure rate, 88.2%); and in 1 patient, a second FMT resulted in cure (secondary cure rate, 94.1%). Late CDI recurrence (≥90 d) was seen in 1 of 17 patients (5.9%) in association with antibiotics and was successfully treated with a repeat FMT. No adverse effects directly related to FMT occurred. Conclusions: FMT was successful and safe in this cohort of patients with severe or complicated CDI. Primary and secondary cure rates were 88.2% and 94.1%, respectively.